2020
DOI: 10.1002/jsfa.10903
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan coatings reduce fruit fly (Anastrepha obliqua) infestation and development of the fungus Colletotrichum gloeosporioides in Manila mangoes

Abstract: BACKGROUND Mangoes are tropical fruits appreciated worldwide but are extremely perishable, being susceptible to decay, pest infestation and fungal diseases. Using the flavorful and highly valued ‘Manila’ cultivar, we examined the effect of second‐generation chitosan coatings on shelf‐life, phenolic compound variation, phytohormones, pest infestation by fruit flies (Anastrepha obliqua) and anthracnose disease caused by the fungus Colletotrichum gloeosporioides. RESULTS We observed almost total elimination of A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Postharvest treatment of mangoes with chitosan revealed downregulated abscisic acid and jasmonic acid levels in the peels, concomitant with a significantly extended shelf life. An infection experiment with C. gloeosporioides showed that anthracnose lesions were significantly smaller on fruits treated with chitosan compared to ones treated with acetic acid and water [58].…”
Section: Abscisic Acidmentioning
confidence: 97%
“…Postharvest treatment of mangoes with chitosan revealed downregulated abscisic acid and jasmonic acid levels in the peels, concomitant with a significantly extended shelf life. An infection experiment with C. gloeosporioides showed that anthracnose lesions were significantly smaller on fruits treated with chitosan compared to ones treated with acetic acid and water [58].…”
Section: Abscisic Acidmentioning
confidence: 97%
“…(2007) also found that chitosan presented a potent inhibition of fungal germination and development. This result was the same with the research of Limon et al (2021) where C.…”
Section: Determination Of the Efficiency Of Chitosan Coating Containi...supporting
confidence: 91%
“…In addition, chitosan effectively enhanced the activities of chitinase and -1,3-glucanase and retard mango ripening (Jitareerat et al, 2007;Jongsri et al, 2017). Limon et al (2021) found that mango fruit coated with chitosan solution also reduced the size of C.…”
Section: Chitosanmentioning
confidence: 94%
“…When applied to grapes, chitosan did not inhibit C. capitata but stimulated oviposition by this fruit fly [ 54 ]. Studies conducted after oviposition revealed that chitosan inhibited the development of eggs and larvae of A. ludens and A. obliqua in mangos [ 52 , 77 ].…”
Section: Discussionmentioning
confidence: 99%